Implementation of Hayzine Media-Based Cultural Literacy Education through P-5 Integration in Education Learning - Feri Tirtoni; Achmad Fandra Maulana; Ayyu Lailuki Azma; Icha Ariskafitriani; Nurul Aisah Lailatuz Zuhriyah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This research discusses the implementation of Heyzine flipbook-based digital media in the subject of Pancasila Education, which is integrated with the Pancasila Student Profile Strengthening Project (P5). The aim is to improve cultural literacy and student engagement in learning through a more interesting and interactive approach. The method used in this research is qualitative, with observation techniques and in-depth interviews involving teachers, students, and parents. The results show that Heyzine media is effective in improving students' understanding and motivation to learn, especially because it is practical and easily accessible through digital devices. In addition, the integration of P5 encourages the development of 21st century skills, such as critical thinking, independence, and collaboration. The conclusion of this study confirms that the utilization of Heyzine as a digital teaching media is relevant in the context of Pancasila education in the digital era.